Research on application of compliant control of smart meter box handling robot - Jiang, Yang; Yu, Yifan; Zhang, Hai-yan; Sun, Da-kang; Li, Zi-heng (Energy reports, 2023)
To solve the problem that the intelligent meter box may collide in the transportation workflow, the paper studies the collision detection of the cooperative robot. Firstly, the architecture and mechanical structure of the collaborative robot intelligent meter box push–pull system is analyzed. Secondly, using the relationship between joint torque and selection LuGre model of joint friction modeling. The second-order external moment observer is constructed based on the robot’s dynamics and generalized momentum equation. Furthermore, the performance of the external moment observer is optimized, and the real-time performance and anti-interference ability of the collision detection algorithm is improved by introducing PD control and speed feedback control. Finally, the results of the designed experiments reveal that the collision detection functions are better realized using the generalized momentum observer method.